2023
DOI: 10.1007/s11119-023-10096-8
|View full text |Cite
|
Sign up to set email alerts
|

End-to-end 3D CNN for plot-scale soybean yield prediction using multitemporal UAV-based RGB images

Sourav Bhadra,
Vasit Sagan,
Juan Skobalski
et al.

Abstract: Crop yield prediction from UAV images has significant potential in accelerating and revolutionizing crop breeding pipelines. Although convolutional neural networks (CNN) provide easy, accurate and efficient solutions over traditional machine learning models in computer vision applications, a CNN training requires large number of ground truth data, which is often difficult to collect in the agricultural context. The major objective of this study was to develope an end-to-end 3D CNN model for plot-scale soybean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 100 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…However, researchers should note that the more complexity increases in data collection and model architecture, the more it costs the practitioners to implement. A higher model complexity and finer spatiotemporal resolution of UAV remote sensing did not necessarily improve crop yield prediction accuracy in deep learning models [77,82]. Furthermore, although deep learning models outperformed traditional statistical and machine learning models, the degree of model performance improvements is sometimes not substantial, and the ultimate model performance generally scored at the moderate level.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, researchers should note that the more complexity increases in data collection and model architecture, the more it costs the practitioners to implement. A higher model complexity and finer spatiotemporal resolution of UAV remote sensing did not necessarily improve crop yield prediction accuracy in deep learning models [77,82]. Furthermore, although deep learning models outperformed traditional statistical and machine learning models, the degree of model performance improvements is sometimes not substantial, and the ultimate model performance generally scored at the moderate level.…”
Section: Discussionmentioning
confidence: 92%
“…Another study on wheat yield prediction indicated that although the RMSE values decreased by approximately 0.06 t ha −1 in the CNN model compared to the linear regression model based on the vegetation index (i.e., enhanced vegetation index 2), the degree of the prediction accuracy improvement in the CNN was not substantial [77]. The most recent work developed soybean yield prediction using multitemporal UAV-based RGB images and more complicated CNN models, but the most efficient model showed a moderate yield prediction accuracy (R 2 = 0.6) [82]. A CNN generally requires hundreds or thousands of training datasets, which may hinder practical phenotyping applications.…”
Section: Biomass and Yieldmentioning
confidence: 96%
“…Crop management can also use CNNs trained to find patterns starting with sample images. A 3D CNN was used to predict soybean yield via analysing multitemporal images [141].…”
Section: Crop Managementmentioning
confidence: 99%
“…Artificial Intelligence(AI) contributed to various field such as biomedical [3][4], agriculture, education and fintech [2][5][6] [7]. There is a Tremendous interest towards aggrotech field in terms of automated farm management, drone for field inspection followed by spray of pesticide [1] [8]. Disease detection is an important stage in consideration of plant life cycle mostly diseases noticed in the stem and leaf, it is a challenging task for individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Global food insecurity is raising concern for humanity due to raise in global warming and population led to a demand supply gap in food production [1]. In terms of food security in recent days playing an important role in addressing the root causes associated with yield [2].…”
Section: Introductionmentioning
confidence: 99%